Experimental and Numerical Study on Fracture Characteristics of Interface between In Situ Engineered Cementitious Composites and Steel Deck - Weiwei Han; Shuyin Wu; Xue Gao; Xinyao Zong; Jingsong Shan (Advances in Materials Science and Engineering)
In this study, engineered cementitious composite (ECC) is used as the pavement of orthotropic steel deck bridge and an epoxy adhesive is used to achieve wet-bonding between the steel deck and cast-in-place ECC. To investigate the fracture properties of bimaterial interface, the double cantilever beam (DCB) and 4-point end notched flexure (4ENF) specimens were used to obtain the fracture toughness, and virtual crack closure technology (VCCT) was used to calculate the energy release rates. A mixed fracture criterion was also established based on the blister test in this study. In addition, for the phenomena of water accumulation in the interface cracks, the hydrodynamic pressure under load was evaluated with a two-way fluid-solid coupling model and the propagation mechanism of cracks at the water-bearing interface was explored. The results showed that the energy release rates at the crack front showed obvious nonuniform distribution characteristics. The blister test indicated that a mixed fracture was in good agreement with the linear fracture criterion. The fracture effect produced by the hydrodynamic pressure of the interfacial water-bearing crack was far less than the fracture toughness of the interface, which indicated that the hydrodynamic pressure could hardly destroy the interface at one time but might cause the erosion fatigue damage of the interface.